Comparing the Effect of Eight Weeks of Resistance and Endurance Trainings on Physiological and Functional Factors and Record of Elite Runners - Ali Asqar Saberi; Merdad Fathi; Keyvan Hejazi (Biyumikānīk-i varzishī, 2020)
Objective: The 3000-meter run is one of the most popular events among endurance and semi-endurance track runnings. Due to its special conditions, aerobic and anaerobic energy production systems can be used at the same time. The aim of the present study was to compare the effect of eight weeks of resistance and endurance trainings on physiological and functional factors and record of elite runners. Methods: In this quasi-experimental study, 22 male elite runners were randomly assigned into the two groups of resistance (n=11) and endurance (n=11) trainings. The resistance and endurance trainings programe was performed for 8 weeks, 3 sessions per week, each for 55-60 minutes. Physiological and functional factors were measured at baseline and at the end of the study. Repeated measures ANOVA was used for within-group and between-group comparisons considering the significant level at P<0.05. Results: The training led to significant improvement in heart rate, blood pressure, muscle strength, muscle endurance, balance and 3000-meter record in both groups. There was a significant difference between groups in the mentioned factors (P<0.05). Conclusion: Both resistance and endurance trainings may have a positive effect on runners’ records and performance indicators.